Konstruksi Pemahaman Konsumen Terhadap Hotel Syariah di Yogyakarta - Syafi'i, Imam; Nurulloh, Muhammad (JOM, 2024)
This study aims to examine the halal ecosystem and the reasons consumers choose sharia-labeled hotels in Yogyakarta. The halal industry has become a global trend, affecting various products that previously did not require halal labeling, such as sharia/halal hotels and others. This research employs a qualitative method with a field research approach, utilizing interviews and observations of sharia hotel consumers in Yogyakarta. The theoretical framework used is Peter L. Berger's social construction theory. The results indicate that halal culture has become a global trend and influences consumer decisions in choosing products or services, including sharia-labeled hotels in Yogyakarta. The increase in the number of sharia-labeled hotels in Yogyakarta is influenced by the growing awareness of halal (sharia) labeling among Indonesians. Additionally, Yogyakarta's reputation as a tourist and educational city necessitates the presence of sharia-labeled hotels to accommodate Muslim tourists. Several reasons consumers choose sharia hotels include proximity and more affordable prices. However, consumers' understanding of the religious importance of halal is a primary factor influencing their decision to choose sharia-labeled hotels over non-sharia-labeled ones. Muslim consumers' awareness of the significance of halal and their sense of comfort when staying at a sharia-licensed hotel are the main determining factors in this preference.